Evaluation, ranking and positioning of measurement methods for pellet production. (August 2018) - Konrád, K.; Viharos, Zs.J.; Németh, G.
Highlights: A deficit is appointed on raw materials qualification of pellets' standards. Ranging methodology is proposed for measuring pellets' raw materials. Devices, time-requirement and measurement complexity are considered in the ranking. Methods for measuring structural components of pellets' raw materials are proposed. The proposed measurement solutions are positioned along the pellet production chain. Abstract: Pellet production and consumption are steadily increasing as a renewable energy source. The production and combustion properties of pellets are defined by molecular structure and elemental composition of raw materials. Quality control tools are different in terms of areas they cover the pellet-production cycle, but considering the raw materials, they regulate only the origin but not the components. There are standardized methods for measuring the biomass and these methods are mainly capable to the pellet raw material qualification, too. Using these together with the control and diagnostics of production parameters, the finished pellet quality (parameters) can be forecasted with high accuracy. A novel evaluation methodology is proposed in the paper for the measurement and qualification of the raw material. The introduced evaluation ranks these methods, based on measuring device-needed, time-requirement and measurement complexity triad. Moreover, the proposed best measurement solutions are positioned along the pellet production chain.